Experimental Analysis on the Properties of Concrete Brick With Partial Replacement of Sand by Saw Dust and Partial Replacement of Coarse Aggregate by Expanded Polystyrene - Ghimire, Anjana; Maharjan, Sanjeev (Journal of Advanced College of Engineering and Management, 2019)
An experimental study had been conducted to study the effects of saw dust and EPS as partial replacement of sand and coarse aggregate in various percentages such as 0%, 10%, 20% and 30% in concrete brick samples of M20 and M15 Grade. Compressive strength, Bulk density and Water absorption of prepared saw dust and EPS M20 and M15 concrete brick were determined. The properties of materials were first determined before the conduction of experimental works. The normal consistency, initial and final setting time and compressive strength of cement used for the experiment were found as 31%,115 minutes, 265 minutes and 39.5 N/mm2 respectively. Sieve analysis to determine the particle size distribution of sand, coarse aggregates, saw dust and EPS was performed. From the sieve analysis, the nominal maximum size of sand, coarse aggregate, saw dust and EPS used for preparing concrete brick sample were 2.36 mm, 12.5 mm, 2.36 mm and 4.75 mm respectively. Impact value of coarse aggregate obtained was 11.20 %.The experimental results showed that water absorption of prepared M15 and M20 concrete brick samples increased with increase in percentage replacement of sand by saw dust and EPS by coarse aggregate. Compressive strength and Bulk density of prepared M15 and M20 concrete brick sample decreased with increase in percentage content of saw dust and EPS. The results showed that the partial replacement of sand by saw dust and coarse aggregate by EPS in concrete brick sample had sufficient strength as compared to common bricks.